Covidization of Media and Entertainment Industry: Current Times and the Future Ahead: A Case Study on The Walt Disney Company - Bhat, Romica; Sarkar, Prithu (Indonesian Journal of Social Science Research, 2022)
The paper has tried to address the modification and adaptation done by the motion pictures industry on the business model, decision-making process, and revenue model, with a case study on Walt Disney. This paper also tried to understand the digital disruptiveness probable strategies taken by media organizations to conquer the spot of market leader and gain a competitive advantage from the set of homogeneous competitors. The new normal business model that has helped Disney+ to create the core competency has given the organization a long-term benefit to make a sustainable business model. The paper further indulges on how Walt Disney’s proactive, informed, and balanced decision-making process about the sudden change in media business dynamics along with the arts and communication industry is going to be a benchmark while keeping the window of both online and offline media business with growing target audience and revenue generation. In the end, we have tried to come up with a business model for the media industry in contemporary times and the future.